Acute effects of extended interval training on countermovement jump and handgrip strength performance in endurance athletes: postactivation potentiation - Garcia-Pinillos, F.; Soto-Hermoso, V. M.; Latorre-Román, P. A. (The Journal of Strength and Conditioning Research, 2015)
The purpose of this study was to analyze multiple effects of an extended interval training (EIT) protocol on countermovement jump (CMJ) and handgrip strength in endurance athletes and to determine the relationship between fatigue and potentiation. Thirty experienced sub-elite male long-distance runners (age = 28.26 ± 8.27 years, body mass index = 22.24 ± 2.50 kg/m^2, and VO2max= 58.7 ± 4.50 ml/kg/min) participated voluntarily in this study. Subjects performed the protocol on an outdoor running track, which consisted of 12 runs of 400 m, grouped into 4 sets of 3 runs, with a passive recovery of 1 minute between runs and 3 minutes between sets (4 × 3 × 400 m). During protocol, fatigue parameters (lactate, heart rate, and rate of perceived exertion) and performance parameters (CMJ, handgrip strength, and time spent in each 400-m run) were controlled. Analysis of variance revealed a significant improvement in CMJ (p < 0.001) throughout the protocol. Cluster analysis grouped according to whether potentiation was experienced (responders group, n = 17) or not (nonresponders group, n = 13) in relation to CMJ change from rest to fatigued condition at the end of activity. Responders group significantly improved (p ? 0.05) the performance in CMJ, handgrip strength and time spent in each 400-m run. Results suggest that despite induced fatigue for EIT, trained subjects can maintain their strength and power levels and their work capacity. This fact would support the rationale that improvements in performance may be due not only to metabolic adaptations but also to specific neuromuscular adaptations. Therefore, the evaluation of power should be considered simultaneously with running performance when monitoring endurance athletes.